Uncovering the role of education in the uptake of preventive measures against Malaria in the African population - Elisabeth Kempter; Neha Bhardwaj Upadhayay (University of Tübingen, Faculty of Economics and Social Sciences, 2022)
In many African countries where malaria is endemic, this life-threatening disease is a leading cause of death. What role does education, in particular numeracy and literacy, play in malaria prevention and treatment-seeking? In this study we apply a birth cohort approach, which allows us to cover a time span of 60 years, and therefore, to provide a comprehensive view on the evolution of malaria prevention and treatment-seeking attitudes adapted among sub-Saharan African cohorts born during the 20th century. We use three different indicators to measure malaria control behavior: the share of respondents using insecticide-treated bednets (ITNs), the share of pregnant women taking antimalarial drugs, and the share of respondents taking their child to a medical facility when suffering from malaria symptoms like fever and cough. Our descriptive results suggest that younger birth cohorts are more likely to adapt malaria control measures than older ones. Based on a sample of 33 African countries, 407 regions, and a total of 1,960 observations, we perform multiple regressions using the pooled OLS estimator. We find that being numerate as well as being literate is positively associated with malaria protection and health-seeking behavior, though the numeracy coefficients are of larger magnitudes indicating that numeracy is at least as important as literacy. While malaria prevention and treatmentseeking behavior is complex and influenced by unobservables, we cannot control for, we account for the most relevant factors like gender, socio-economic status, topology, and urbanrural settings. Our findings show that in addition to education, the involvement of women in health-care decision-making, as well as the exposure to media, is positively correlated with malaria control. On the other hand, we find that a low socio-economic status makes the adaption of adequate malaria prevention and treatment-seeking behavior more difficult. In highly elevated regions and regions with lower precipitation, where malaria is less prevalent, people seem to pay less attention to protection measures. Finally, while malaria is more acute in rural regions, in urban areas antimalarial drugs are also commonly used for protection.
urn:nbn:de:bsz:21-dspace-1307884; hdl:10900/130788
Keywords: H75; I12; I15; I18; 330; malaria; sub-Saharan Africa; insecticide-treated bednets (ITNs); numeracy; literacy